Effects and Interferences of Emicizumab, a Humanised Bispecific Antibody Mimicking Activated Factor VIII Cofactor Function, on Coagulation Assays - Adamkewicz, Joanne I.; Chen, David C.; Paz-Priel, Ido (Thrombosis and Haemostasis, 2019)
Emicizumab bridges activated factor IX (FIX) and FX to restore the tenase function mediated by activated FVIII (FVIIIa), which is deficient in people with haemophilia A (PwHA). Unlike FVIII, emicizumab does not require activation to function; thus, in coagulation assays, the behavior of emicizumab may differ from that of FVIII. The objective of this study was to assess the effect of emicizumab on coagulation assays, including potential interference behavior that may produce inaccurate or misleading results. A variety of clotting-based, amidolytic/chromogenic, latex particle-enhanced turbidometric, and enzyme-linked immunosorbent methods were investigated. As expected based on its pharmacologic mechanism of action, emicizumab exhibited strong activity on the activated partial thromboplastin time (aPTT), which resulted in interference with several aPTT-based assays, most importantly the one-stage FVIII activity assay; these assays are not recommended for PwHA receiving emicizumab therapy. Pharmacodynamic activity of emicizumab, as measured by FVIII chromogenic assays, was species-dependent due to the binding specificity of the drug antibody. Outside of FVIII assays, emicizumab did not interfere with assays based on immunologic or chromogenic principles, nor with clotting assays based on nonintrinsic pathway activators, thus offering alternative choices where aPTT-based assays might otherwise be used. The observed interferences are in line with the unique mechanism of action of emicizumab. Potential interferences should be taken into account in the selection of coagulation assays and interpretation of coagulation assay test results for PwHA receiving emicizumab therapy.
Keywords: emicizumab; haemophilia A; blood coagulation factors; coagulation assays; interference